Les impasses théoriques et pratiques du contrôle de constitutionnalité canadien - Gervais, Marc-Antoine (McGill Law Journal, 2021)
This article proposes a new interpretation of section 52 of the Constitution Act, 1982. It argues that the legal effect of this provision depends on the type of unconstitutionality at issue. On the one hand, subsection 52(1) governs substantive conflicts between constitutional and legislative norms by rendering inoperative legislation that is incompatible with the supreme law. On the other hand, subsection 52(3) requires the observance of the procedural rules prescribed by the Constitution. Legislative measures that contravene this procedural criterion are ultra vires and, as a result, invalid. This article further attempts to clarify the effects of declarations of unconstitutionality on third parties as well as their temporal operation. It contends that declaratory judgments of unconstitutionality are in rem in nature. Such declarations bind parties to the litigation and third parties alike by virtue of the principle of res judicata, subject to rare exceptions. The general scope of declarations of unconstitutionality allows courts to adjust the temporal operation of the law deemed unconstitutional, notably to maintain the security and stability of legal relationships.